Anti-fouling and antibacterial particle full-body ceramic rock plate and preparation method thereof
By filling the holes of the grained ceramic rock slabs with multiple layers of hydrophobic and antibacterial materials, the problem of insufficient anti-fouling and antibacterial properties of the rock slabs is solved, and better anti-fouling and long-lasting antibacterial effects are achieved.
Patent Information
- Application Number
- CN202411940634.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
The anti-fouling performance of the grained ceramic rock slabs is insufficient, and watermarking is prone to occur, and the antibacterial effect is short-lasting.
By filling the holes with a first fill layer of hydrophobic, a second fill layer, a third fill layer of hydrophobic and protective layer from the inside to the outside, a multi-layer antifouling and antibacterial structure is formed using materials such as wetting agents, hydrophobic modifiers, ceramic powders, silicon sols and antibacterial agents.
It significantly improves the anti-fouling effect and durability of ceramic rock slabs, avoids the occurrence of watermarking, and extends the durability of antibacterial properties.
Smart Images

Figure CN119874410A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic technology, and in particular to an anti-fouling and antibacterial granular ceramic rock plate and a preparation method thereof. Background Art
[0002] The size of the colored particles used for decorative effect in the granular ceramic slab is generally 1 to 5 mm, which is relatively large. Therefore, during the pressing process of the colored particles, larger initial holes will be formed, resulting in more and larger numbers and sizes of closed-cell holes remaining in the body after firing. Please refer to Figure 1 After the granular ceramic rock slab is finely polished, more holes will be exposed.
[0003] At present, the conventional silica sol filling and hydrophobic coating treatment process is difficult to meet the anti-fouling requirements of granular ceramic rock slabs. This is because the surface holes of granular ceramic rock slabs are numerous and large, resulting in the inability of traditional anti-fouling treatment to fill all the holes at one time. Figure 2 Holes that are not completely filled require multiple long-term grinding and filling to meet the requirements. In addition, since the silica sol used is super hydrophilic, when the surface of the rock plate is filled with too much silica sol, even if the surface is coated with a hydrophobic coating, it is difficult for the hydrophobic coating to block highly adsorbable pollutants such as ink.
[0004] Furthermore, since there is a large amount of hydrophilic silica sol on the surface of the stone slab and the bottoms of some deeper holes are not completely filled, when clean water stays on the surface for a few minutes, it will penetrate into the gaps in the holes, affecting the scattering and reflection of light, and producing a transparency and color change similar to that of a piece of paper after it gets wet. This phenomenon is called a "watermark". Although the shadow will disappear due to water evaporation in the next few minutes, it does cause trouble to consumers.
[0005] In addition, in the process of brightening and antifouling treatment of ceramic stone slabs, antibacterial agents are usually added to give the product antibacterial properties. During the use of the product, antibacterial ions will gradually migrate to the surface to kill or inhibit bacteria and gradually be consumed. At the same time, antibacterial agents will also be lost as the surface of the product wears, which weakens the antibacterial properties of the product. Therefore, it is still necessary to consider how to extend the service life of antibacterial stone slabs. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide an anti-fouling and antibacterial granular ceramic rock plate and a preparation method thereof, aiming to solve the technical problems in the prior art of insufficient anti-fouling performance of granular ceramic rock plates, watermark generation and short durability of antibacterial effect.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides an anti-fouling and antibacterial granular ceramic rock plate, wherein the holes on the anti-fouling and antibacterial granular ceramic rock plate are filled with a first filling layer, a second filling layer, a third filling layer and a protective layer from the inside to the outside; the raw materials for preparing the first filling layer include: a wetting agent, a first hydrophobic modifier and an antibacterial agent; the raw materials for preparing the second filling layer include: ceramic powder and an adhesive; the raw materials for preparing the third filling layer include: silica sol, a second hydrophobic modifier and an antibacterial agent; the raw materials for preparing the protective layer include: an organic silicone hydrophobic agent.
[0009] The anti-fouling and antibacterial granular ceramic rock board, wherein the wetting agent includes at least one of polyether-modified polysiloxane and silicone-modified acrylate.
[0010] The anti-fouling and antibacterial granular ceramic rock plate, wherein the first hydrophobic modifier and the second hydrophobic modifier respectively include at least one of sodium methyl silicate, potassium methyl silicate, and lithium methyl silicate.
[0011] The anti-fouling and antibacterial granular ceramic rock board, wherein the ceramic powder includes at least one of aluminum oxide, silicon oxide, and glass powder.
[0012] The anti-fouling and antibacterial granular ceramic rock board, wherein the particle size distribution of the ceramic powder is: D50 is 5-10μm, D10 is greater than 1μm, and D90 is less than 20μm.
[0013] The anti-fouling and antibacterial granular ceramic rock board, wherein the adhesive includes at least one of sodium silicate, potassium silicate, and lithium silicate; the modulus of the adhesive is 3.0 to 3.5.
[0014] The anti-fouling and anti-bacterial particles throughout the ceramic rock plate, wherein the antibacterial agent is nano silver wire or nano silver particles.
[0015] The second aspect of the present invention provides a method for preparing a granular ceramic rock plate, which is used to prepare the anti-fouling and antibacterial granular ceramic rock plate as described above, comprising the following steps:
[0016] S001. Polish the surface of the ceramic rock plate;
[0017] S002. Add the first solution dropwise to the surface of the ceramic rock plate, apply pressure and polish, so that the first solution enters the holes on the surface of the ceramic rock plate to form a first filling layer; the raw materials for preparing the first solution include, by weight: 0.3 to 0.8 parts of a wetting agent, 12 to 20 parts of a first hydrophobic modifier solution, and 78.2 to 87.7 parts of water; the mass percentage concentration of the first hydrophobic modifier solution is 20% to 25%; the raw materials for preparing the first solution also include an antibacterial agent;
[0018] S003. Add the second solution dropwise to the surface of the ceramic rock plate, pressurize and grind, so that the second solution enters the holes on the surface of the ceramic rock plate to form a second filling layer; the raw materials for preparing the second solution include: 5 to 15 parts of ceramic powder, 1 to 2 parts of adhesive, and 86 to 101 parts of water, by weight;
[0019] S004. Add the third solution dropwise to the surface of the ceramic rock plate, apply pressure and polish, so that the third solution enters the holes on the surface of the ceramic rock plate to form a third filling layer; the raw materials for preparing the third solution include: 40 to 60 parts of silica sol, 10 to 25 parts of the second hydrophobic modifier solution, and the rest is water, with a total of 100 parts; the mass percentage concentration of the silica sol is 25%; the mass percentage concentration of the second hydrophobic modifier solution is 20% to 25%; the raw materials for preparing the third solution also include an antibacterial agent;
[0020] S005. Add silicone hydrophobic agent to the surface of the ceramic rock plate and grind it under pressure to form a protective layer.
[0021] The method for preparing the granular ceramic rock slab is as follows: in the first solution, the concentration of the antibacterial agent is 4 to 6 mg / ml; in the third solution, the concentration of the antibacterial agent is 1 to 2 mg / ml.
[0022] The method for preparing the granular ceramic rock plate, wherein the amount of the first solution added is 10 to 20 g / m 2 The amount of the second solution added is 20 to 30 g / m 2 The amount of the third solution added is 50 to 70 g / m 2 The amount of the organic silicon hydrophobic agent added is 4 to 8 g / m 2 .
[0023] Beneficial effects: The first aspect of the present invention provides an anti-fouling and antibacterial granular ceramic rock plate, which has the effects of hydrophobicity, efficient filling and long-lasting antibacterial by filling the holes from the inside to the outside with a hydrophobic first filling layer, a tight second filling layer, a hydrophobic third filling layer and a protective layer, thereby improving the anti-fouling effect and durability and avoiding the "watermark" phenomenon.
[0024] The second aspect of the present invention provides a method for preparing a granular ceramic rock plate, which is used to prepare the anti-fouling and antibacterial granular ceramic rock plate as described above. The preparation method can be implemented using existing equipment, has strong controllability, and requires fewer coatings, effectively improving the anti-fouling treatment efficiency of the surface of the granular ceramic rock plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the surface microstructure of the granular ceramic rock slab after fine polishing.
[0026] Figure 2 This is a picture of the holes on the surface of the granular ceramic rock slab that are not completely filled.
[0027] Figure 3 This is the particle size distribution diagram of the quartz powder used in Example 1.
[0028] Figure 4 This is the particle size distribution diagram of the glass powder used in Example 2.
[0029] Figure 5 This is the watermark test result.
[0030] Figure 6 This is the surface state of the product in Comparative Example 4 before and after the antifouling coating scrubbing test. DETAILED DESCRIPTION
[0031] The present invention provides an anti-fouling and antibacterial granular ceramic rock plate and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] A first aspect of the present invention provides an anti-fouling and antibacterial granular ceramic rock plate, wherein the holes on the anti-fouling and antibacterial granular ceramic rock plate are filled from inside to outside with a first filling layer, a second filling layer, a third filling layer and a protective layer;
[0033] The raw materials for preparing the first filling layer include: a wetting agent, a first hydrophobic modifier and an antibacterial agent;
[0034] The raw materials for preparing the second filling layer include: ceramic powder and adhesive;
[0035] The raw materials for preparing the third filling layer include: silica sol, a second hydrophobic modifier and an antibacterial agent;
[0036] The raw materials for preparing the protective layer include: an organic silicon hydrophobic agent.
[0037] To address the "watermark" problem, the first hydrophobic modifier in the first filling layer of the present invention can directly penetrate into the pores under the action of the wetting agent to form a hydrophobic pore wall, thereby hindering the deep penetration of water and avoiding the "watermark" problem.
[0038] The second filling layer uses ceramic powder to perform preliminary filling. Compared with the waxing operation, that is, pure use of silica sol to fill the holes, the filling efficiency of ceramic powder with larger particle size will be higher. The adhesive is used to increase the bonding strength between ceramic particles and the pore walls, while improving the durability of surface gloss and anti-fouling ability.
[0039] The third filling layer is filled with silica sol, so as to further improve the hole filling efficiency. The third filling layer also contains a second hydrophobic modifier, which cooperates with the first filling layer to play a multiple hydrophobic role.
[0040] The antibacterial agents in the first filling layer and the third filling layer play multiple antibacterial roles. When the antibacterial ions on the surface are consumed, the antibacterial ions inside can continue to diffuse outward, thereby maintaining the effective concentration of the antibacterial ions for a long time.
[0041] Preferably, the wetting agent includes at least one of polyether-modified polysiloxane and silicone-modified acrylate.
[0042] Preferably, the first hydrophobic modifier and the second hydrophobic modifier respectively include at least one of sodium methyl silicate, potassium methyl silicate and lithium methyl silicate. By introducing the hydrophobic modifier into the micropores, the penetration of water-based pollutants can be suppressed during use, playing an anti-fouling role, and also suppressing the "watermark" phenomenon. In addition, the components selected in this embodiment are all water-based hydrophobic modifiers, which are different from the hydrophobic modifiers of silicone oil emulsions or pure silicone oils. The water-based hydrophobic modifier is in a hydrophilic state before drying, and will not affect the subsequent coating of the water-based coating during subsequent processing.
[0043] In the third filling layer, methyl silicate and silica sol will also undergo a certain polymerization reaction through hydroxyl groups, so that the third filling layer has a better hydrophobic effect, thereby enhancing the resistance to pollutants.
[0044] Preferably, the ceramic powder includes at least one of aluminum oxide, silicon oxide and glass powder.
[0045] Preferably, the particle size distribution of the ceramic powder is: D50 is 5 to 10 μm, D10 is greater than 1 μm, and D90 is less than 20 μm. Particles that are too coarse cannot enter the holes to fill them, and may also produce large scratches on the surface of the rock slab. Particles that are too small will fill the shallower tiny pits on the surface of the rock slab. Due to the lack of mechanical bite force of the pore wall, ceramic powders with too small a particle size are easy to fall off later. The present invention determines the particle size distribution of the ceramic powder as above by combining the size of the holes on the surface of the rock slab.
[0046] Preferably, the adhesive includes at least one of sodium silicate, potassium silicate and lithium silicate.
[0047] Among the above three adhesives, compared with sodium silicate, potassium silicate and lithium silicate have more stable performance and avoid the salt frost whitening phenomenon, so potassium silicate and lithium silicate can be used preferentially.
[0048] Preferably, the modulus of the adhesive is 3.0 to 3.5. Silicates with too low a modulus have a slow drying speed and poor water resistance and scrub resistance, while silicates with too high a modulus have poor adhesion and are easy to powder after drying.
[0049] The second aspect of the present invention provides a method for preparing a granular ceramic rock plate, which is used to prepare the anti-fouling and antibacterial granular ceramic rock plate as described above, comprising the following steps:
[0050] S001. Polish the surface of the ceramic rock plate;
[0051] S002. Add the first solution dropwise to the surface of the ceramic rock plate, apply pressure and polish, so that the first solution enters the holes on the surface of the ceramic rock plate to form a first filling layer; the raw materials for preparing the first solution include, by weight: 0.3 to 0.8 parts of a wetting agent, 12 to 20 parts of a first hydrophobic modifier solution, and 78.2 to 87.7 parts of water; the mass percentage concentration of the first hydrophobic modifier solution is 20% to 25%; the raw materials for preparing the first solution also include an antibacterial agent;
[0052] Specifically, the surface tension coefficient of water at 20°C is 72.8mN / m. On the surface of the ceramic substrate, especially the inner wall of the micropores, it is difficult for water to fully wet and spread. By adding a wetting agent, the surface tension of the aqueous solution can be reduced to 15-20mN / m, greatly improving the pore-entry performance of the aqueous solution, so that effective ingredients such as water-based hydrophobic modifiers and antibacterial agents can enter the micropores on the surface of the ceramic substrate. The amount of wetting agent added should not be too low, otherwise the surface tension will not be significantly reduced, and too much addition will not continuously improve the wetting effect, but will also increase costs;
[0053] S003. Add the second solution dropwise to the surface of the ceramic rock plate, pressurize and grind, so that the second solution enters the holes on the surface of the ceramic rock plate to form a second filling layer; the raw materials for preparing the second solution include: 5 to 15 parts of ceramic powder, 1 to 2 parts of adhesive, and 86 to 101 parts of water, by weight;
[0054] S004. Add the third solution dropwise to the surface of the ceramic rock plate, apply pressure and polish, so that the third solution enters the holes on the surface of the ceramic rock plate to form a third filling layer; the raw materials for preparing the third solution include: 50 parts of silica sol, 10 to 25 parts of the second hydrophobic modifier solution, and the rest is water, with a total of 100 parts; the mass percentage concentration of the silica sol is 25%; the mass percentage concentration of the second hydrophobic modifier solution is 20% to 25%; the raw materials for preparing the third solution also include an antibacterial agent;
[0055] If the dosage of the second hydrophobic modifier, such as methyl silicate, is too low, the hydrophobic effect will be poor, while if it is too high, the curing speed will be slow and the cost will increase.
[0056] S005. Add silicone hydrophobic agent to the surface of the ceramic rock plate and grind it under pressure to form a protective layer.
[0057] Specifically, the first solution, the second solution and the third solution can be pressurized and polished onto the surface of the ceramic rock plate through a nylon fiber wheel and enter into the holes. At the same time, the surface temperature is raised to 70-90°C through the friction between the nylon fiber wheel and the surface of the ceramic rock plate, thereby forming the first filling layer, the second filling layer and the third filling layer respectively; the silicone hydrophobic agent can be coated with a sponge grinding head to form a protective layer.
[0058] Preferably, in the first solution, the concentration of the antibacterial agent is 4-6 mg / ml; in the third solution, the concentration of the antibacterial agent is 1-2 mg / ml.
[0059] Preferably, the antibacterial agent is nanosilver wire or nanosilver particle. Nanosilver antibacterial agent has the characteristics of high activity and does not affect the appearance of the rock board after coating, and is very suitable for the preparation of antibacterial ceramic products, but its high activity also means that it is easy to be consumed and lost. The present invention can continuously maintain the antibacterial effect on the surface of the rock board by setting a gradient concentration so that the deep holes contain more antibacterial agent as a source of silver ions.
[0060] Preferably, the amount of the first solution added is 10 to 20 g / m 2 , 2 to 4 drippers can be used to complete the dripping;
[0061] The amount of the second solution added is 20 to 30 g / m 2 , 4 to 6 drippers can be used to complete the dripping;
[0062] The amount of the third solution added is 50-70 g / m 2 , 16 to 20 drippers can be used to complete the dripping;
[0063] The amount of the organic silicon hydrophobic agent added is 4 to 8 g / m 2 , 1 to 2 drippers can be used to complete the dripping.
[0064] The present invention is further described with reference to the following examples and comparative examples.
[0065] Example 1
[0066] A ceramic rock plate with anti-fouling and antibacterial particles, the preparation method of which comprises the following steps:
[0067] A001. Wetting agent (polyether modified polysiloxane, model: 8000), potassium methyl silicate solution and water are mixed in a mass ratio of 0.4:15:84.6 to obtain a first solution, and a nano silver wire antibacterial agent is added to the first solution to make the nano silver wire antibacterial agent concentration of the first solution be 6 mg / ml;
[0068] The mass percentage concentration of the potassium methyl silicate solution is 25%;
[0069] A002. The quartz powder, lithium silicate water glass and water were mixed in a mass ratio of 10:6:84 to obtain a second solution;
[0070] Wherein, the mass percentage concentration of lithium silicate water glass is 20%, and the modulus is 3.5;
[0071] Quartz powder is a type of silicon oxide, and its particle size distribution is D50 is 5.7μm, D10 is 1.7μm, and D90 is 18.4μm. Figure 3 is the particle size distribution diagram of quartz powder;
[0072] A003. The silica sol (mass percentage concentration of 25%), the sodium methyl silicate solution (mass percentage concentration of 20%) and water were mixed in a mass ratio of 50:13:47 to obtain a third solution, and the nano silver wire antibacterial agent was added to the third solution so that the nano silver wire antibacterial agent concentration of the third solution was 1.5 mg / ml;
[0073] A004. Prepare a polished and dried ceramic rock plate with particles throughout the body, and sequentially apply the first solution, the second solution, the third solution and the silicone hydrophobic agent dropwise to the surface of the ceramic rock plate in a waxing machine and polish it;
[0074] The first solution was dripped using two drippers, and the dripping amount was controlled at 12 g / m 2 The second solution was added by 4 drippers, and the amount of dripping was controlled at 20g / m 2 The third solution was added by 18 drippers, and the amount of dripping was controlled at 50g / m 2 ; The silicone hydrophobic agent is added by a dripper, and the amount of dripping is controlled at 5g / m 2 ;
[0075] The first solution, the second solution, and the third solution are all pressurized and polished onto the surface of the ceramic rock slab through a nylon fiber wheel, and the surface temperature of the rock slab is increased to 70-90°C through the friction between the nylon fiber wheel and the surface of the ceramic rock slab; finally, a sponge grinding head is used to coat the organosilicon hydrophobic agent to finally obtain the anti-fouling and antibacterial granular ceramic rock slab.
[0076] Example 2
[0077] A ceramic rock plate with anti-fouling and antibacterial particles, the preparation method of which comprises the following steps:
[0078] A001. A wetting agent (silicone-modified acrylate, model: BYK-3550), sodium methyl silicate solution and water were mixed in a mass ratio of 0.6:12:87.4 to obtain a first solution, and a nano silver wire antibacterial agent was added to the first solution so that the concentration of the nano silver wire antibacterial agent in the first solution was 4 mg / ml;
[0079] The mass percentage concentration of the potassium methyl silicate solution is 25%;
[0080] A002. The glass powder, potassium silicate water glass and water were mixed in a mass ratio of 10:6:84 to obtain a second solution;
[0081] Wherein, the mass percentage concentration of potassium silicate water glass is 20%, and the modulus is 3.0;
[0082] The particle size distribution of the glass powder is: D50 is 6.1μm, D10 is 2.9μm, D90 is 8.1μm, Figure 4 is the particle size distribution diagram of glass powder;
[0083] A003. The silica sol (mass percentage concentration of 25%), potassium methyl silicate solution (mass percentage concentration of 20%) and water are mixed in a mass ratio of 50:20:30 to obtain a third solution, and the nano silver wire antibacterial agent is added to the third solution so that the concentration of the nano silver wire antibacterial agent in the third solution is 2 mg / ml;
[0084] A004. Prepare a polished and dried ceramic rock plate with particles throughout the body, and sequentially apply the first solution, the second solution, the third solution and the silicone hydrophobic agent dropwise to the surface of the ceramic rock plate in a waxing machine and polish it;
[0085] The first solution was dripped using 4 drippers, and the dripping amount was controlled at 20g / m 2 The second solution was added by 4 drippers, and the amount of dripping was controlled at 25g / m 2 The third solution was added by 16 drippers, and the amount of dripping was controlled at 50g / m 2 ; The silicone hydrophobic agent is added by a dripper, and the amount of dripping is controlled at 5g / m 2 ;
[0086] The first solution, the second solution, and the third solution are all pressurized and polished onto the surface of the ceramic rock slab through a nylon fiber wheel, and the surface temperature of the rock slab is increased to 70-90°C through the friction between the nylon fiber wheel and the surface of the ceramic rock slab; finally, a sponge grinding head is used to coat the organosilicon hydrophobic agent to finally obtain the anti-fouling and antibacterial granular ceramic rock slab.
[0087] Comparative Example 1
[0088] A ceramic rock plate with anti-fouling and antibacterial particles, the preparation method of which comprises the following steps:
[0089] A001. The silica sol (mass percentage concentration of 25%) and water were mixed in a mass ratio of 50:50 to obtain a fourth solution, and the nano silver wire antibacterial agent was added to the fourth solution so that the nano silver wire antibacterial agent concentration of the fourth solution was 2 mg / ml;
[0090] A002. Prepare a polished and dried ceramic rock slab with particles throughout the body, and sequentially apply the fourth solution and the silicone hydrophobic agent dropwise to the surface of the ceramic rock slab in a waxing machine and polish it;
[0091] The above steps are repeated 3 times to achieve complete filling of the pores on the surface of the product with silica sol;
[0092] In the waxing machine, the fourth solution was dripped with 44 drippers, and the total dripping amount was controlled at 180g / m 2 ; The silicone hydrophobic agent is dripped with 4 drippers, and the total dripping amount is controlled at 6g / m 2 ;
[0093] The fourth solution is pressurized and polished onto the surface of the ceramic rock plate by a nylon fiber wheel; the organic silicon hydrophobic agent is coated by a sponge grinding head to obtain the anti-fouling and antibacterial particles throughout the ceramic rock plate.
[0094] Comparative Example 2
[0095] A ceramic rock plate with anti-fouling and antibacterial particles, the preparation method of which comprises the following steps:
[0096] A001. Wetting agent (polyether modified polysiloxane, model: 8000), potassium methyl silicate solution and water are mixed in a mass ratio of 0.4:15:84.6 to obtain a first solution, and a nano silver wire antibacterial agent is added to the first solution to make the nano silver wire antibacterial agent concentration of the first solution be 6 mg / ml;
[0097] The mass percentage concentration of the potassium methyl silicate solution is 25%;
[0098] A002. Silica sol (mass percentage concentration of 25%), sodium methyl silicate solution (mass percentage concentration of 20%) and water were mixed in a mass ratio of 50:13:47 to obtain a third solution, and a nanosilver wire antibacterial agent was added to the third solution so that the nanosilver wire antibacterial agent concentration of the third solution was 1.5 mg / ml;
[0099] A003. Prepare a polished and dried ceramic rock plate with particles throughout the body, and sequentially apply the first solution, the third solution and the silicone hydrophobic agent dropwise to the surface of the ceramic rock plate in a waxing machine and polish it;
[0100] The first solution was dripped using two drippers, and the dripping amount was controlled at 12 g / m 2 The third solution was dripped using 26 drippers, and the dripping amount was controlled at 120g / m 2 ; The silicone hydrophobic agent is added by two drippers, and the amount of dripping is controlled at 6g / m 2 ;
[0101] The first solution and the third solution are both pressurized and polished onto the surface of the ceramic rock slab through a nylon fiber wheel, and the surface temperature of the rock slab is increased to 70-90°C through the friction between the nylon fiber wheel and the surface of the ceramic rock slab; finally, a sponge grinding head is used to coat the organosilicon hydrophobic agent to finally obtain the anti-fouling and antibacterial granular ceramic rock slab.
[0102] Comparative Example 3
[0103] A ceramic rock plate with anti-fouling and antibacterial particles throughout, which differs from Example 1 in that the particle size distribution of quartz powder is different. In this comparative example, the particle size distribution of quartz powder is: D50 is 41.8 μm, D10 is 13.1 μm, and D90 is 103.6 μm.
[0104] Comparative Example 4
[0105] A ceramic rock plate with anti-fouling and antibacterial particles throughout, which differs from Example 1 in that the particle size distribution of quartz powder is different. In this comparative example, the particle size distribution of quartz powder is: D50 is 0.8 μm, D10 is 0.1 μm, and D90 is 7.2 μm.
[0106] Comparative Example 5
[0107] A ceramic rock slab with anti-fouling and antibacterial particles throughout, which differs from Example 1 in that step A001 is missing.
[0108] The various properties of the anti-fouling and antibacterial granular ceramic rock slabs prepared in the above embodiments and comparative examples were tested.
[0109] The antifouling performance test method is as follows: add 5 ml of black blue ink to the surface of the slate, 10 locations at a time, wipe off the ink at one location with a towel and washing powder every 20 minutes, and observe the ink residue;
[0110] Watermark observation: add 10ml of clean water to the surface of the rock board, 3 locations each time, leave it for 30 minutes, then use a dry towel to check the water drops at all locations to see if there are any watermarks;
[0111] Antibacterial durability test: Use a scrub resistance tester, use a 5% detergent solution as the detergent, and use a hard sponge grinding head to scrub back and forth on the surface of the rock plate. The total number of times is controlled to 20,000 times. Then refer to JC / T 897-2014 "Antibacterial Performance of Antibacterial Ceramic Products" for antibacterial performance testing, and use Escherichia coli as the bacterial species;
[0112] Evaluation of wear resistance: Use an optical microscope to observe the integrity of the coating on the surface of the rock slab after the antibacterial durability test, and then evaluate the firmness of the coating adhesion.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115]
[0116] From the results in Table 1, it can be seen that for antifouling performance, since the first solution and the third solution containing the aqueous hydrophobic modifier component are used to fill the holes in Example 1, Example 2, Comparative Example 2 and Comparative Example 4 to form an antifouling coating, the antifouling coating has a hydrophobic and anti-penetration effect from the inside to the outside, and thus has excellent anti-ink penetration ability, and the antifouling time reaches a maximum value of 200 minutes, while Comparative Example 1 using conventional treatment has the worst antifouling performance. In addition, since Comparative Example 2 does not use the second solution for filling, the silica sol is not fully filled in the holes on the surface of the product, which makes it easy to hide dirt in the antifouling test, so the anti-fouling time is relatively short.
[0117] As for the watermark problem, in the test examples using water-based hydrophobic modifiers, the watermark problem was well solved. Figure 5 As shown, the sample of Example 1 has no obvious watermark, while the watermark of Comparative Example 1 is very obvious. In Comparative Example 5, since the third solution contains a hydrophobic modifier, the watermark problem is still well suppressed, and only a slight watermark appears.
[0118] As for the antibacterial performance, since Examples 1, 2 and Comparative Examples 2, 3, and 4 all adopted a dual-gradient antibacterial agent loading process, they exhibited excellent antibacterial durability.
[0119] As for the wear resistance, in Examples 1 and 2, ceramic particles with suitable particle sizes were used, which could be firmly filled in the holes, and no overly fine powder adhered to the shallower pits. The silica sol in the subsequent third solution had a nanoparticle size and stronger adhesion, which was more suitable for filling the shallower pits, thereby obtaining a firmly bonded antifouling coating, so that the surface coating could remain intact after the wear resistance test; while in Comparative Example 4, due to the use of overly fine ceramic particles, its adhesion to the ceramic rock plate substrate was weak, resulting in partial detachment after the test, such as Figure 6 shown.
[0120] In addition, since the second solution containing ceramic powder is used for filling in the embodiment, the filling efficiency of the surface holes is improved. Therefore, compared with Comparative Example 1, the amount of the third solution containing silica sol in Example 1 and Example 2 is greatly reduced, which effectively shortens the anti-fouling treatment time and reduces material and labor costs.
[0121] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.
Claims
1. A ceramic rock board with anti-fouling and antibacterial particles, characterized in that: The holes on the anti-fouling and antibacterial granule-through ceramic rock plate are filled from the inside to the outside with a first filling layer, a second filling layer, a third filling layer and a protective layer; The raw materials for preparing the first filling layer include: a wetting agent, a first hydrophobic modifier and an antibacterial agent; The raw materials for preparing the second filling layer include: ceramic powder and adhesive; The raw materials for preparing the third filling layer include: silica sol, a second hydrophobic modifier and an antibacterial agent; The raw materials for preparing the protective layer include: an organic silicon hydrophobic agent.
2. The anti-fouling and anti-bacterial granular ceramic rock board according to claim 1 is characterized in that: The wetting agent includes at least one of polyether-modified polysiloxane and silicone-modified acrylate.
3. The anti-fouling and anti-bacterial granular ceramic rock board according to claim 1 is characterized in that: The first hydrophobic modifier and the second hydrophobic modifier respectively include at least one of sodium methyl silicate, potassium methyl silicate, and lithium methyl silicate.
4. The anti-fouling and anti-bacterial granular ceramic rock board according to claim 1 is characterized in that: The ceramic powder includes at least one of aluminum oxide, silicon oxide and glass powder.
5. The anti-fouling and anti-bacterial granular ceramic rock board according to claim 1 is characterized in that: The particle size distribution of the ceramic powder is as follows: D50 is 5 to 10 μm, D10 is greater than 1 μm, and D90 is less than 20 μm.
6. The anti-fouling and anti-bacterial granular ceramic rock board according to claim 1 is characterized in that: The adhesive includes at least one of sodium silicate, potassium silicate and lithium silicate; the modulus of the adhesive is 3.0-3.
5.
7. The anti-fouling and anti-bacterial granular ceramic rock board according to claim 1 is characterized in that: The antibacterial agent is nano silver wire or nano silver particle.
8. A method for preparing a granular ceramic rock plate, for preparing the antifouling and antibacterial granular ceramic rock plate as claimed in any one of claims 1 to 7, comprising the following steps: S001. Polish the surface of the ceramic rock plate; S002. Add the first solution dropwise to the surface of the ceramic rock plate, pressurize and polish, so that the first solution enters the holes on the surface of the ceramic rock plate to form a first filling layer; The raw materials for preparing the first solution include, by weight: 0.3 to 0.8 parts of a wetting agent, 12 to 20 parts of a first hydrophobic modifier solution, and 78.2 to 87.7 parts of water; the mass percentage concentration of the first hydrophobic modifier solution is 20% to 25%; the raw materials for preparing the first solution also include an antibacterial agent; S003. Add the second solution dropwise to the surface of the ceramic rock plate, pressurize and grind, so that the second solution enters the holes on the surface of the ceramic rock plate to form a second filling layer; the raw materials for preparing the second solution include: 5 to 15 parts of ceramic powder, 1 to 2 parts of adhesive, and 86 to 101 parts of water, by weight; S004. Add the third solution dropwise to the surface of the ceramic rock plate, apply pressure and polish, so that the third solution enters the holes on the surface of the ceramic rock plate to form a third filling layer; the raw materials for preparing the third solution include: 40 to 60 parts of silica sol, 10 to 25 parts of the second hydrophobic modifier solution, and the rest is water, with a total of 100 parts; the mass percentage concentration of the silica sol is 25%; the mass percentage concentration of the second hydrophobic modifier solution is 20% to 25%; the raw materials for preparing the third solution also include an antibacterial agent; S005. Add silicone hydrophobic agent to the surface of the ceramic rock plate and grind it under pressure to form a protective layer.
9. The method for preparing the granular ceramic rock board according to claim 8, characterized in that: In the first solution, the concentration of the antibacterial agent is 4-6 mg / ml; in the third solution, the concentration of the antibacterial agent is 1-2 mg / ml.
10. The method for preparing the granular ceramic rock board according to claim 8, characterized in that: The amount of the first solution added is 10 to 20 g / m 2 The amount of the second solution added is 20 to 30 g / m 2 The amount of the third solution added is 50 to 70 g / m 2 The amount of the organic silicon hydrophobic agent added is 4 to 8 g / m 2 .